2020
DOI: 10.3390/app10103436
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Data Acquisition System for Pinch Grip Assessment Based on Fugl Meyer Protocol: A Feasibility Study

Abstract: The Upper Extremity Fugl Meyer Assessment (UE-FMA) is the most comprehensive assessment for pinch impairment after stroke. The pinch test of UE-FMA is manually performed by pulling a pincer object away from the patient’s fingers while providing a visual observation that results in a subjective assessment. In this study, an automated data acquisition system that consists of a linear electric actuator applying automatic pulling to the customized pincer object held by the volunteer was developed. The pinch force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The 12 presented papers in this second volume are grouped according to their contributions to the main parts of the monitoring and control engineering scheme applied to human health applications, namely papers focusing on measuring/sensing of physiological variables [5][6][7][8], papers describing health monitoring applications [9][10][11][12], and finally, examples of control applications for human health [13][14][15][16]. As indicated by Aerts [1], it is envisioned that the field of human health engineering is complementary to the field of biomedical engineering as it not only contributes to developing technology for curing patients or supporting chronically ill people, but also covers applications on healthy humans (e.g., sports, sleep, and stress) and thus also focuses on disease prevention and optimizing human well-being more generally.…”
Section: Main Content Of the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The 12 presented papers in this second volume are grouped according to their contributions to the main parts of the monitoring and control engineering scheme applied to human health applications, namely papers focusing on measuring/sensing of physiological variables [5][6][7][8], papers describing health monitoring applications [9][10][11][12], and finally, examples of control applications for human health [13][14][15][16]. As indicated by Aerts [1], it is envisioned that the field of human health engineering is complementary to the field of biomedical engineering as it not only contributes to developing technology for curing patients or supporting chronically ill people, but also covers applications on healthy humans (e.g., sports, sleep, and stress) and thus also focuses on disease prevention and optimizing human well-being more generally.…”
Section: Main Content Of the Special Issuementioning
confidence: 99%
“…Al-Halhouli et al [6] demonstrated the feasibility of using a wearable and stretchable inkjet-printed strain gauge sensor for estimating respiratory rate, which is a key vital sign variable in many medical and health applications. In their study, Alsayed et al [7] developed an automated data acquisition system for measuring pinch and pulling forces in patients recovering from stroke. Nishio et al [8] investigated a method for quantifying the functional decline in proprioceptors in patients with low back pain using vibrations with sweep frequencies covering the entire range of response frequencies of proprioceptors.…”
Section: Main Content Of the Special Issuementioning
confidence: 99%
“…Furthermore, they do not include sensors to track the slipping that occurs on the pencil object during the pinch assessment. Therefore, the pinch strength data in this study were collected using a pinch–pull gripping system previously developed [ 17 , 18 ]. Figure 2 depicts the developed system, which mainly consists of a pincer object, linear actuator, pulling force load cell, pinch force load cell, and linear variable differential transformer (LVDT) sensor.…”
Section: Introductionmentioning
confidence: 99%